2012
DOI: 10.1016/j.biocel.2011.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin signalling in pulmonary fibrosis

Abstract: A large body of evidence demonstrates that angiotensin II and angiotensin receptors are required for the pathogenesis of experimental lung fibrosis. Angiotensin has a number of profibrotic effects on lung parenchymal cells that include the induction of growth factors for mesenchymal cells, extracellular matrix molecules, cytokines and increased motility of lung fibroblasts. Angiotensin is also proapoptotic for lung epithelial cells, and is synthesized by a local system (i.e. entirely within the lung tissue) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
101
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 25 publications
2
101
1
4
Order By: Relevance
“…Increased NF-κB activation and its target genes Agt and IL-1β are observed in lungs with pulmonary fibrosis (44,45). A genome-wide association study previously reported that an SNP variation in TLE1 was associated with colitis, and a case was made that this might be due to TLE1 interacting with NOD2 and inhibiting NF-κB activation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Increased NF-κB activation and its target genes Agt and IL-1β are observed in lungs with pulmonary fibrosis (44,45). A genome-wide association study previously reported that an SNP variation in TLE1 was associated with colitis, and a case was made that this might be due to TLE1 interacting with NOD2 and inhibiting NF-κB activation (16).…”
Section: Discussionmentioning
confidence: 99%
“…A key event involved in the pathogenesis of PF is apoptotic cell death of the lung parenchyma (43). It is believed that an altered RAS is a potent inducer of pulmonary apoptosis (44,45). Recent data suggest that ACE2 inhibits apoptosis of alveolar epithelial cells to exert antifibrotic effects (46).…”
Section: Discussionmentioning
confidence: 99%
“…The balance between the opposing effector molecules angiotensin II (AngII) and angiotensin- (1)(2)(3)(4)(5)(6)(7) [Ang-(1-7)] may play a pivotal role in determining cardiovascular pathogenesis and lung fibrosis (32,42,43). After the conversion of angiotensinogen into angiotensin (AngI) by renin, AngII is generated by conversion of AngI by angiotensin converting enzyme (ACE).…”
mentioning
confidence: 99%